Effect of high-temperature/current stress on the forward tunneling current of InGaN/GaN high-power blue-light-emitting diodes. (10th July 2017) - Liu, Sheng; Zheng, Chenju; Lv, Jiajiang; Liu, Mengling; Zhou, Shengjun
Abstract: Through the analysis of the temperature-dependent current–voltage ( I – V ) characteristics of the fabricated InGaN/GaN high-power blue-light-emitting diodes (LEDs), the low-bias region was confirmed to be dominated by tunneling current, while the medium-bias region was dominated by diffusion-recombination current. Electrons and heavy holes appeared to play similar roles in the tunneling current of the fabricated LEDs, with no apparent dominant tunneling entity determined by characteristic energy as previous works suggested. After 1000 h of high-temperature/current stress, the medium-bias regions of the I – V curves of LEDs remained almost unchanged, while the current in the low-bias region was greatly enhanced by the stress, which confirmed the different carrier transport mechanism behaviors in the low- and medium-bias regions. Further comparison between the I – V characteristics of the unstressed and stressed LEDs suggested that the change in I – V curve was associated with the increase in defect density and the apparent doping concentration in the InGaN/GaN multiple-quantum-well (MQW) active region.